2006
DOI: 10.1227/01.neu.0000222817.99752.e6
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Complications Of External Ventricular Drainage

Abstract: Hemorrhagic complications of EVD placement are more common than previously suspected. Admitting diagnosis seems to have an effect on the development of an associated hemorrhage and its size. Catheter gauge has an effect on hematoma volume. Most of the hemorrhages seen on postinsertion computed tomographic scans do not cause detectable changes in the clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
8
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 28 publications
8
80
8
3
Order By: Relevance
“…However, no allergic reactions were reported in either of the groups and no evident neurotoxic side effects of silver particles were observed in the group with SI catheters. The overall surgical complication rate of 7 % (Table 1) fits in the lower median as reported in literature (range 1-33 %) [3,15,16]. Following a retrospective evaluation of surgical complication rates at the Department of Neu-rosurgery of the University Hospital Zurich [3], a standardized surgical and handling protocol was estab-lished which enabled to reduce the surgical complication rate from 10 to 7 %.…”
Section: Discussionsupporting
confidence: 62%
“…However, no allergic reactions were reported in either of the groups and no evident neurotoxic side effects of silver particles were observed in the group with SI catheters. The overall surgical complication rate of 7 % (Table 1) fits in the lower median as reported in literature (range 1-33 %) [3,15,16]. Following a retrospective evaluation of surgical complication rates at the Department of Neu-rosurgery of the University Hospital Zurich [3], a standardized surgical and handling protocol was estab-lished which enabled to reduce the surgical complication rate from 10 to 7 %.…”
Section: Discussionsupporting
confidence: 62%
“…This rate is comparable to previously reported rates for hemorrhagic complication among cohorts for whom routine postprocedural CT images were obtained. 4,13 In our study, 75% of the positive CT findings were either punctate or small foci of hemorrhage (Grades 1 and 2). We did not observe significant increases in EVD-associated hemorrhagic complications among patients who received prophylaxis within 24 hours of their procedure or before their procedure.…”
Section: Discussionmentioning
confidence: 47%
“…Interestingly, studies have also suggested that larger catheters may result in smaller hemorrhage volumes compared with smaller catheters, possibly through a tamponade effect. 14,19 Midline shift is a marker of unilateral pressure exerted on an unevenly distributed ventricular system in the setting of elevated intracranial pressure, which could result in ipsilateral ventricular decompression after EVD placement and obstruction of the catheter due to collapsed ventricular ependyma. In addition, this study validates the classic teaching of the FoM as the preferred target for EVD placement.…”
Section: Discussionmentioning
confidence: 99%